Biofuel Feedstocks: The Risk of Future Invasions - DiTomaso, Joseph M.; Barney, Jacob N.; Fox, Alison M. (Council for Agricultural Science and Technology (CAST), 2007)
In an effort to reduce greenhouse gas emissions, expand domestic energy production, and maintain economic growth, public and private investments are being used to pursue dedicated feedstock crops for biofuel production. This commentary addresses the necessary balance between designing biofuel feedstock crops to require minimal inputs yet preventing them from surviving outside the cultivated environment.